Violence at work and ways of eliminating it in light of ILO Convention No. 190 - Bartosik, Zuzanna (Undesirable Phenomena in Employment from the Perspective of Labour Law - Selected Issues, 2023)
This study investigates the new definition of violence and harassment included in ILO Convention No. 190 and selected measures for its elimination provided in the convention act. These proposals have been compared with the currently binding Polish regulations. The aim of the study is to conduct a comparison and to show how laconic and oftentimes imprecise – in relation to the demands formulated in the convention Polish regulations remain in many respects. The paper will highlight the most intriguing solutions provided for by the convention, yet not currently implemented in the Polish legal system.